Nggusu Waru Local Wisdom as an Ethical Framework for Gender-Inclusive and Child-Friendly Social Transformation in the Context of Social Development in Bima Society - Nurbayan, ST; Wahyuni, Wahyuni (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Gender inequality and the vulnerability of women and children remain structural and cultural problems in many regions of Indonesia, including Bima. Various government policies have not yet been fully effective, as their implementation does not always align with the local values embedded in society. Nggusu Waru, a form of local wisdom from Bima that embodies eight moral principles related to knowledge, integrity, social responsibility, and the protection of vulnerable groups, actually holds significant potential as an ethical framework for promoting more gender-just social development. However, these values have experienced a decline in meaning due to modernization and the lack of cultural regeneration. This conceptual article proposes the integration of Nggusu Waru into social development through processes of value re-articulation, participatory approaches, and mainstreaming into village-level policies. Theoretical analysis indicates that gender inequality can only be addressed effectively when structural change is accompanied by transformation in social norms. By integrating gender theory, social norms theory, cultural capital, and Participatory Action Research (PAR) methodology, this article formulates a conceptual model that positions Nggusu Waru as a value-based foundation for strengthening the protection of women and children, enhancing women’s participation in the public sphere, and fostering a new, more egalitarian social culture. This integration is not merely an effort at cultural preservation, but a pragmatic, contextual, and sustainable strategy of social transformation aimed at creating a women-friendly and child-caring environment within Bima society.